Lilo & Stitch - Spencer, Clark; Sanders, Chris (Christopher Michael); Deblois, Dean.; Chase, Daveigh; Carrere, Tia.; Stiers, David Ogden; McDonald, Kevin, 1961-; Rhames, Ving, 1961-; Walt Disney Pictures; Walt Disney Feature Animation (Firm); Walt Disney Studios Home Entertainment (Firm) (Burbank, CA : Distributed by Walt Disney Studios Home Entertainment, 2009)
An evil creator has created a little creature by genetic experimentation. The creator and creature are sent to prison. The creature escapes and heads for Earth where he tries to impersonate a dog. Bent on self preservation, he plans to use a human shield to protect him from the aliens sent to recapture him. Earth girl, Lilo, adopts the 'dog, ' gives him the name Stitch and actually developes an emotional attachment to the little creature. Lilo's dysfunctional family consists only of her sister Nani, but the two are about to be ripped apart by social worker Cobra Bubbles. Stitch as the new family member brings quite some action into all their lifes, and after a while, not even the aliens can recognize their former target.
Title from container.
Originally released as a motion picture in 2002.
Special features: Deleted scenes; "Your 'Ohana" music video featuring The Hawaiian Chorus; "The story room:" an interactive behind-the-scenes look at the making of the film; Lilo & Stitch Island Adventure games; "A Stitch in time:" follow Stitch through the Disney years; "I can't help fallin in love with you" music video performed by A- Teens; DisneyPedia: Hawaii: the islands of Aloha: explore the Hawaiian Islands.
Editor, Darren T. Holmes ; music, Alan Silvestri, Mike Tavera.
Voices: Daveigh Chase, Christopher Michael Sanders, Tia Carrere, David Ogden Stiers, Kevin McDonald, Ving Rhames.
MPAA rating: PG; for mild sci-fi action.
Keywords: Science -- Experiments -- Drama; Girls -- Hawaii -- Drama; Sisters -- Hawaii -- Drama; Pet adoption -- Hawaii -- Drama; Families -- Hawaii -- Drama; Action and adventure films; Fantasy films; Video recordings for the hearing impaired; Feature films